Factors associated with being asked to initiate someone into injection drug use. (1st April 2015) - Bluthenthal, Ricky N.; Wenger, Lynn; Chu, Daniel; Lorvick, Jennifer; Quinn, Brendan; Thing, James P.; Kral, Alex H.
Highlights: PWID are often asked to initiate injection-naïve persons into injection drug use. Describing injection to and injecting around non-PWID may lead to initiation request. Reducing injection socializing behaviors among PWID might prevent injection uptake. Abstract: Aims: Injection drug use initiation typically involves an established person who injects drugs (PWID) helping the injection-naïve person to inject. Prior to initiation, PWID may be involved in behaviors that elevate injection initiation risk for non-injectors such as describing how to inject and injecting in front of injection-naïve people. In this analysis, we examine whether PWID who engage in either of these behaviors are more likely to be asked to initiate someone into drug injection. Methods: Interviews with PWID ( N  = 602) were conducted in California between 2011 and 2013. Multivariate analysis was conducted to determine factors associated with being asked to initiate someone. Results: The sample was diverse in terms of age, race/ethnicity, and drug use patterns. Seventy-one percent of the sample had ever been asked to initiate someone. Being asked to initiate someone was associated with having injected in front of non-injectors (Adjusted Odds Ratio [AOR] = 1.80, 95% Confidence Interval [CI] = 1.12, 2.91), having described injection to non-injectors (AOR = 3.63; 95% CI = 2.07, 6.36), and doing both (AOR = 9.56; 95% CI = 4.43, 20.65) as compared to doing neither behavior (referent). Being female (AOR = 1.73; 95% CI = 1.10, 2.73) and non-injection prescription drug misuse in the last 30 days (AOR = 1.69; 95% CI = 1.12, 2.53) were also associated with having been asked to initiate someone. Conclusion: Reducing initiation into injection drug use is an important public health goal. Intervention development to prevent injection initiation should include established PWID and focus on reducing behaviors associated with requests to initiate injection and reinforcing refusal skills and intentions among established PWID.